Disposition of lead (Pb) in brain of rats following oral exposure to lipstick - Hashemi-Moghaddam, Hamid; Shiravi, Abdolhossein; Shadab Shamsabad, Fereshte; Torabi, Mahbobe; Rezaei Taviraei, Mostafa (Archives of Advances in Biosciences, 2015)
Information about the health risks that might be associated with lipstick consumption effects is scarce in the literature. The present work investigated the bioaccumulation of lead (Pb) in brain of rats originated from lipstick sample. First, Lead contents were determined in 12 different brands of lipsticks. Lead was detected in all the studied samples. The average lead content in 14 lipsticks samples was 12.2 PPM wet wt. Then, one brand was selected for feeding to the rats and amount of oral exposing in the three doses was calculated. Sixty rats were used for the experiment. Animals were divided into 4 groups of 15 animals each. While 1group served as control group, the remaining 3 groups were exposed to lipstick through oral gavage for 12 weeks. Results show that, exposure to the lipstick cause significantly disposition of lead in the brain of rats.